MEAN DIAGNOSTIC DELAY IN PATIENTS PRESENTING WITH HEAD AND NECK CANCER IN A TERTIARY CARE HOSPITAL IN LAHORE (Journal of Medical & Health Sciences Review, 2025)
Objectives: To determine mean diagnostic delay for head and neck cancer among patients presenting at a tertiary care hospital.Study Design: Descriptive analytical study.Place and Duration of Study: “Combined Military Hospital, Lahore from December 2022 to January 2024”.Methodology: Ninety three patients who were diagnosed to have cancer of the head and neck region were included in the study. Careful medical history and meticulous review of clinical records of the patients was performed to determine duration of delay from presentation till definitive diagnosis. Data was analyzed by SPSS 22.00.Results: Median age was 55.00 (82.00 – 11.00) years. There were 56 (60.22%) males and 37 (39.78%) were females. In 46 (49.46%) patients, there was positive history of smoking. Most commonly diagnosed head and neck malignancy was oral squamous cell carcinoma 22 (23.66%). Median patient delay was 5.00 (520.00 – 1.00) weeks. Median professional delay was 8.00 (53.00 – 1.00) weeks. Median total diagnostic delay was 16.00 (540.00 – 3.00) weeks.Conclusion: Average diagnostic delay for head and neck cancer in present study was sixteen weeks.